Finansowe uwarunkowania rozwoju małych i średnich przedsiębiorstw u progu wstąpienia do Unii Europejskiej - Prędkiewicz, Katarzyna (Financial Conditioning of Development of Small and Average Enterprises at Threshold of Access to European Union, 2005)
An article indicates on financial aspects of developing small and medium companies, financial barriers and show how small and medium entrepreneur can overcome them using new possibility which appears in connection with European Union funds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 315-325